Effective Load Balance Scheduling Schemes for Heterogeneous Distributed System - Zeba Khan; Mahfooz Alam; Raza Abbas Haidri (Institute of Advanced Engineering and Science, 2017)
Importance of distributed systems for distributing the workload on the processors is globally accepted. It is an agreed fact that divides and conquers is the effective strategy for load balancing problems. In today’s time, load balancing is the major issue for scheduling algorithm such as in Parallel and Distributed Systems including Grid and Cloud Computing and many more. Load Balancing is the phenomena of spreading or distributing the workload among the processors so that all processors keep busy for all the time, in order to prevent ideal time of processors. In this work, presents a load balancing algorithm for heterogeneous distributed system (HeDS) with aim of minimizing the load imbalance factor (LIF). The proposed algorithm is using optimization techniques such as Max-Max and Min-Max strategy and applied on Folded Crossed Cube (FCC) network. Makespan, speedup and average resource utilization are also evaluated for performance matrices. The experimental results of the proposed algorithms have showed better in comparison to with previous work under various test conditions.